2012
DOI: 10.1111/j.1747-7379.2012.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Contacts and the Economic Performance of Immigrants: A Panel Study of Immigrants in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 64 publications
6
94
0
2
Order By: Relevance
“…It, thus, contributes to the literature by extending it to Germany. In contrast to the most closely related study by Kanas et al (2011), who use data on the level of federal states (Länder ), the ethnic share was observed on the postcode level which allows for a sensible approximation of actual neighbourhoods and social networks. This was achieved by combining the SOEP with small-scale raster data from microm on the ethnic share.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It, thus, contributes to the literature by extending it to Germany. In contrast to the most closely related study by Kanas et al (2011), who use data on the level of federal states (Länder ), the ethnic share was observed on the postcode level which allows for a sensible approximation of actual neighbourhoods and social networks. This was achieved by combining the SOEP with small-scale raster data from microm on the ethnic share.…”
Section: Resultsmentioning
confidence: 96%
“…Most closely related to this paper is a study by Kanas et al (2011) who find no enclave effects in Germany regarding both occupational status and earnings, arguing that possibly a sufficient threshold of the immigrant share is not reached. However, they use the ethnic share on the level of federal states (Länder ) which is likely to be too large to allow for observing any enclave effects as this is certainly beyond the scope of a personal network.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the role social capital plays on employment outcomes of immigrants, a number of studies have shown that having contacts with natives, who are more likely to have better information about the host country labour market and employment opportunities, has a stronger positive effect on immigrants' labour market outcomes compared to those with less/fewer contacts with natives (see Kanas et al, 2012;Hagan 1998 andPutnam 2000;Drever and Hoffmeister 2008;Kazemipur 2006). However, immigrants who have better contacts with co-ethnic groups may also have a positive 5 See Granovetter (1973), Granovetter (1983) and Montgomery (1991).…”
Section: Social Capital and The Labour Marketmentioning
confidence: 99%
“…On the other hand Kanas et al (2012), using German Socio-Economic Panel data to study social contacts of immigrants in Germany, found no evidence that ethnic concentration can improve immigrants' occupational status and wages. Finally, Piracha et al (2014), using data from Australia, found that social capital increases immigrants' entry into the labour market, especially for women and those employed in white-collar occupations, though they found no effect on wages.…”
mentioning
confidence: 99%